2010
DOI: 10.1002/ijc.25589
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Norepinephrine induces VEGF expression and angiogenesis by a hypoxia‐inducible factor‐1α protein‐dependent mechanism

Abstract: A growing number of studies have demonstrated that physiological factors can influence the progression of several cancers via cellular immune function, angiogenesis and metastasis. Recently, stress-induced catecholamines have been shown to increase the expression of various cancer progressive factors, including vascular endothelial growth factor (VEGF), matrix metalloproteinases and interleukins. However, a detailed mechanism remains to be identified. In this study, we investigated the role of adrenergic recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
113
0
9

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(127 citation statements)
references
References 38 publications
5
113
0
9
Order By: Relevance
“…The high levels of D1 expression induced by T3 are consistent with the positive feedback loop of the processes for NE differentiation (47). PKA directly induces the inactivation of an apoptotic factor (phosphorylation of BAD) (9), and it indirectly stimulates VEGF secretion (PI3K/AKT/hypoxia inducible factor-1α [HIF-1α]) (48) and neurite outgrowth by cytoskeleton rearrangements (inhibition of Ras homolog gene family A [RhoA]/Rho-associated protein kinase [ROCK]) (49). PKA also induces the phosphorylation of CREB and the expression of cell survival factors (Bcl-2), metalloproteases and NE peptides (NSE, CgA, SYP, neurotensin and so on) (8,9,36).…”
Section: Discussionsupporting
confidence: 56%
“…The high levels of D1 expression induced by T3 are consistent with the positive feedback loop of the processes for NE differentiation (47). PKA directly induces the inactivation of an apoptotic factor (phosphorylation of BAD) (9), and it indirectly stimulates VEGF secretion (PI3K/AKT/hypoxia inducible factor-1α [HIF-1α]) (48) and neurite outgrowth by cytoskeleton rearrangements (inhibition of Ras homolog gene family A [RhoA]/Rho-associated protein kinase [ROCK]) (49). PKA also induces the phosphorylation of CREB and the expression of cell survival factors (Bcl-2), metalloproteases and NE peptides (NSE, CgA, SYP, neurotensin and so on) (8,9,36).…”
Section: Discussionsupporting
confidence: 56%
“…Results from several recent studies have indicated that stress-induced catecholamines upregulate the synthesis of many proangiogenic factors, such as VEGF, through the b2-AR-mediated signaling pathway in a variety of malignant tumor cells and induce angiogenesis in the tumor tissues (Thaker et al 2006, Madden et al 2011, Park et al 2011. It has also been shown that norepinephrine stimulates the production of MMP2 and MMP9, which mediate extracellular matrix degradation and tissue remodeling and induce angiogenesis, through the b2-AR signaling pathway in tumor cells and tumor-associated macrophages (Cole & Sood 2012).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that chronic restraint stress, which results in high levels of tissue catecholamines, enhanced tumor angiogenesis in primary ovarian tumors by upregulating the expression of VEGF and MMPs, and that a b-blocker reversed stressenhanced angiogenesis, indicating potential roles of catecholamines and the b-adrenergic receptor (b-AR)-mediated signaling pathway in tumor angiogenesis (Thaker et al 2006). Catecholamines induced the expression of HIF1a (HIF1A) under aerobic conditions and stimulated HIF1A-mediated VEGF expression in human breast cancer cells (Park et al 2011). It has also been reported that catecholamines induced the secretion of endogenous proinflammatory cytokines (such as IL1b, IL6, and IL8) and production of MMPs in tumor cells (Elenkov & Chrousos 2002, Johnson et al 2005, Lutgendorf et al 2008, Shahzad et al 2010, Shi et al 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Sood et al also reported that chronic stress induced by daily restrain or ISO injections protected tumor cells from apoptosis upon loss of anchorage and detachment of the extracellular matrix in an orthotopic model of human ovarian cancer. 43 Other studies indicated that bAR stimulation increases the expression of VEGF and angiogenesis in human breast ovarian and melanoma cancer cells 42,44,45 and pro-metastatic matrix metalloproteinases and other inflammatory mediators in gastric tumors. 46 aAR blockade was also shown to block the proliferative effect of catecholamines on breast cancer cells in vitro, 47 although the stimulatory effect of catecholamine on breast cancer cells is not seen in all studies.…”
Section: Chronic Stress Favors Ovarian Prostate and Breast Cancer Bomentioning
confidence: 99%